Political Connections and Social Networks in Targeted Transfer Programmes: Evidence from Rural Ethiopia. - Caeyers, B; Dercon, S (Centre for the Study of African Economies, 2008)
In many developing countries, the beneficiaries of transfer programmes are determined by community-based processes, based on some general targeting rules related to needs. This opens the door for local social and political processes to impact on who gets access. Despite increasingly large scale social protection programmes in Africa, we have limited evidence on the political economy processes involved. We focus on Ethiopia were the local political authorities are in charge of food aid transfers. We investigate whether social networks and political connections matter for access. We find evidence for the hypothesis that the process results in the targeting of households that cannot easily rely on support from relatives or friends. On average, for each additional person the household can rely on in times of need, the probability of this household of obtaining food aid decreases with almost 1 percentage point. We also find strong evidence of political connections and favouritism. Households having close associates holding official positions have, ceteris paribus, more than 10 percent higher probability of obtaining free food than households that are not well connected with powerful households. We do not find evidence for the hypothesis that other social networks in the community influence the food aid allocation process. Finally, investigating reverse causality, we find no evidence that social and political networks are affected by the food aid transfer system.